COMMUNICATION AND CONFLICT IN IPJ X - Daniel Fofiu (Agora International Journal of Economical Sciences (AIJES), 2024)
Optimal communication of the system reveals its advantages also within the Romanian Police. The work of a policeman is based on my own knowledge and communication skills and now that I work in the Ministry of Internal Affairs, I noticed that this opinion has been substantiated and even emphasized. One thing is certain: being part of a law enforcement body is not easy. The criminal environment is highly dangerous and most criminals want to escape impediments that place them outside the limits imposed by law. The policeman is in the crosshairs of the offender. Taking into account all these aspects, the policeman must be in continuous communication, collaboration with other colleagues and develop various methods of identifying those who commit antisocial acts. The greater number of law enforcement teams can lead to deterrence for criminals. Working in the system, I can say that the optimization of the communication process is permanently targeted by police officers and, as a result, many cases can be solved.
Keywords: 330